Design and Simulation of a PV and a PV–Wind Standalone Energy System to Power a Household Application - Panayiotou, Gregoris; Kalogirou, Soteris A.; Tassou, Savvas A. (My University, 2012)
In this paper the design and simulation of two renewable-based standalone energy systems for application in two different locations are carried out. More specifically, the systems examined are a standalone PV system and a standalone hybrid PV–Wind system. The locations considered are those of Nicosia, Cyprus and Nice, France. These two locations have similar Mediterranean climates with different wind potential and slightly different solar irradiation levels which lead to interesting conclusions concerning the application of such systems. Since both systems are standalone, the energy produced is stored in a battery bank. The software used for the modeling and simulation processes is TRNSYS. The results of this paper define the optimal type and size of the renewable-based system to be applied in each of the locations examined at the minimum system cost. Additionally, a comparison of the two systems for both locations in terms of technical and economic aspects is presented where it is concluded that the type of the system to be used in each case is directly depended on the climatic characteristics of the specific location. More specifically, for Nicosia the solely PV system provides a better option than the PV–Wind hybrid system while in Nice the opposite is the case.
Keywords: Computer software; Climatology; Computer simulation; Hybrid systems; Load profile; Solar potential; Wind potential; Standalone Baseline